Pengenalan Echo Enzyme Melalui Program Kuliah Kerja Nyata (KUKERTA) Universitas Riau Untuk Mewujudkan Masyarakat Peduli Lingkungan - Pernantah, Piki Setri; Putrayudha, Rizky Akbar; Alfazar, Tengku Muhammad Bolkiah; Putra, Muhammad Dhias Akhwal; Alchanaru, Ariiqoh; Nurpranawati, Jania Sukma; Yoshikawati, Lolita Britania; Tarindha, Dinisha; Octarainy, Delina; Ginting, I Viola Sandra; Wulandhani, Sri Oktadriantiwi (Journal of Community Engagement Research for Sustainability, 2022)
Eco enzyme is a liquid or organic substance made by fermentation process of organic matter, water, and sugar. Eco enzymes use the rest of the vegetables and fruit peels in the manufacturing process. Although it takes a long time, the principle and use of echo enzyme is great for sustainable environmental protection. This devotional activity aims as an introduction to the application of synthetic chemical efficiency, reducing the use of toxic substances, and sustainable environmental protection, which is generally applied to environmentally friendly chemistry. Eco Enzyme is made by fermentation method and this devotional activity is carried out through learning methods, manufacturing to the dissemination of devotional products. The result of this service is the implementation of the introduction and use of echo enzymes in the local community.